1999
DOI: 10.1007/bf03165428
|View full text |Cite
|
Sign up to set email alerts
|

Reverse redistribution of Tc-99m-tetrofosmin in patients with acute myocardial infarction

Abstract: We examined reverse redistribution (RR) of Tc-99m-tetrofosmin after a single injection in patients with acute myocardial infarction (AMI). Tc-99m-tetrofosmin myocardial SPECT was performed in 28 patients with AMI 10-14 days after the onset. Myocardial images were obtained 30 min and 180 min after the injection of 740 MBq of Tc-99m-tetrofosmin. The left ventricular wall was divided into 9 segments. Regional myocardial uptakes of Tc-99m-tetrofosmin were scored by 4-point scoring (0 = normal, 1 = mildly reduced, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 9 publications
0
13
1
Order By: Relevance
“…Although the present study did not provide such a pathophysiological interpretation, the finding that the mean %CI in regions with RR after exercise was as low as that observed in scarred areas adds to the findings of Sugihara et al, 7 elucidating the clinical significance of RR on 99m Tc-tetrofosmin SPECT imaging.…”
Section: Study Limitationcontrasting
confidence: 70%
See 1 more Smart Citation
“…Although the present study did not provide such a pathophysiological interpretation, the finding that the mean %CI in regions with RR after exercise was as low as that observed in scarred areas adds to the findings of Sugihara et al, 7 elucidating the clinical significance of RR on 99m Tc-tetrofosmin SPECT imaging.…”
Section: Study Limitationcontrasting
confidence: 70%
“…[19][20][21] In patients with AMI who underwent reperfusion therapy, the RR phenomenon has been demonstrated on 99m Tc-labeled flow tracers myocardial scintigraphy and the myocardium that shows the RR phenomenon of 99m Tc-labeled flow tracers is thought to be damaged, though contractile function is preserved to a certain extent. [7][8][9] Sugihara et al 7 reported that the impairment of the LV wall motion in the regions showing the 99m Tc-tetrofosmin RR phenomenon, evaluated using contrast left ventriculography, ranged from akinesis/dyskinesis to normal, but was significantly better than that in the regions with a fixed defect. Takeishi et al 9 had a comparable result for LV wall motion evaluated by contrast left ventriculography in the regions with the 99m Tc-sestamibi RR phenomenon, and both those studies had findings that were similar to those observed in regions with RR on 201 Tl scintigraphy.…”
Section: Reverse Redistribution Phenomenon Of 99m Tc-tetrofosminmentioning
confidence: 99%
“…Reverse redistribution (RRD) was observed between the initial and delayed images of AMI on myocardial perfusion images using a 99m Tc-labeled agent with almost no clearance in normal myocardium, which is reported to reflect mitochondrial damage in myocardium [14][15][16][17]. It has also been reported that RRD can predict functional recovery in the chronic phase.…”
Section: Introductionmentioning
confidence: 93%
“…However, these studies assessing myocardial uptake of 99m Tc-labeled agents were conducted using visual semi-quantitative analysis. Moreover, left ventricular function was assessed using left ventriculography (LVG) or echocardiography [14][15][16][17][18][19][20][21]. The findings of these studies on RRD were, therefore, not necessarily valid.…”
Section: Introductionmentioning
confidence: 99%
“…Arii et al [12] reported that reverse redistribution of 99m Tc-tetrofosmin is more prominent in the infarct area. Sugihara et al [13] reported that reverse redistribution of 99m Tc-tetrofosmin indicates salvaged myocardium. The present study was performed to investigate the time evolution of the 99m Tc-tetrofosmin reverse redistribution pattern and its relation to regional wall motion in patients with acute myocardial infarction; in addition, we aimed to assess the clinical implications of this phenomenon.…”
Section: Introductionmentioning
confidence: 98%